Critical Discourse Analysis on News Tribun Jabar about Thousands of Workers Slide the Palace - David Darwin; Yumna Rasyid; Miftahulkhairah Anwar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The quantity and quality of strikes and labor demonstrations has increased since the fall of the Suharto regime. This is not only because of the increasingly oppressed conditions of workers, but also because the space for freedom of organization is increasingly wide open. Almost every day the mass media reported on strikes and demonstrations of workers. However, until now, not much is known about how the workers' actions are represented by the mass media. Therefore, it is necessary to investigate this issue. This study aims to determine how strikes and labor demonstrations are represented by the mass media. This research uses content analysis method. The object of the research is the news on strikes and labor demonstrations published in Tribun Jabar, during 2000. The unit of analysis that is coded is the physical position of the news, the format of the news, the nature of the news, the source of the news, the news frame, and the orientation of the news. The findings of this study are that the newspapers that are the subject of this research, the layout of the pages rarely places the news of the labor strike on pages other than page one such as page 2, page 19, page 24, and so on. This study also found that they like to choose straight news news format and the nature of hard news news. The media tend to use labor as the main source of their news. Then, the frame used to report the news of the labor strike is an anarchic frame that is usually used by employers in responding to various issues surrounding labor strikes and the frame for violations of labor rights which is usually used by workers in interpreting various industrial conflict events. Finally, the orientation is on events rather than issues in telling the actions of workers' strikes.